Phantasmatic Indochina : French colonial ideology in architecture, film, and literature - Norindr, Panivong, 1961- (Asia-Pacific., 1996)
This reflection on colonial culture argues for an examination of "Indochina" as a fictive and mythic construct, a phantasmatic legacy of French colonialism in Southeast Asia. Panivong Norindr uses postcolonial theory to demonstrate how French imperialism manifests itself not only through physical domination of geographic entities, but also through the colonization of the imaginary. In this careful reading of architecture, film, and literature, Norindr lays bare the processes of fantasy, desire, and nostalgia constituent of French territorial aggression against Indochina. Analyzing the first Exposition Coloniale Internationale, held in Paris in 1931, Norindr shows how the exhibition's display of architecture gave a vision to the colonies that justified France's cultural prejudices, while stimulating the desire for further expansionism. He critiques the Surrealist counter-exposition mounted to oppose the imperialist aims of the Exposition Coloniale, and the Surrealist incorporation and appropriation of native artifacts in avant-garde works. According to Norindr, all serious attempts at interrogating French colonial involvement in Southeast Asia are threatened by discourse, images, representations, and myths that perpetuate the luminous aura of Indochina as a place of erotic fantasies and exotic adventures. Exploring the resilience of French nostalgia for Indochina in books and movies, the author examines work by Malraux, Duras, and Claudel, and the films Indochine, The Lover, and Dien Bien Phu. Certain to impact across a range of disciplines, Phantasmatic Indochina will be of interest to those engaged in the study of the culture and history of Vietnam, Cambodia, Thailand, and Laos, as well as specialists in the fields of French modernism, postcolonial studies, cultural studies, and comparative literature.--